Enantiospecific synthesis of both enantiomers of the longtailed mealybug pheromone and their evaluation in a new zealand vineyard - Ramesh, Remya; Bell, Vaughn; Twidle, Andrew M.; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2015)
The irregular monoterpenoid sex pheromone of Pseudococcus longispinus and its enantiomer were prepared from the corresponding bornyl acetates. The use of readily accessible chiral starting materials and lactone lactone rearrangement are the highlights of the present synthesis. The biological activities of the two enantiomers and racemic mixture were tested in a New Zealand vineyard. The (S)-(+)-enantiomer was significantly more attractive to P. longispinus males than the racemic mixture or the (R)-(-)-enantiomer.